2014
DOI: 10.1186/1471-2369-15-159
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between asymptomatic organ damage, and serum soluble tumor necrosis factor-like weak inducer of apoptosis (sTWEAK) and Interleukin-17A (IL-17A) levels in non-diabetic hypertensive patients

Abstract: BackgroundThis study aimed to measure the serum soluble tumor necrosis factor-like weak inducer of apoptosis (sTWEAK) and interleukin-17A (IL-17A) levels in hypertensive patients with/without asymptomatic organ damage (AOD), as well as to determine the relationship between the serum sTWEAK and IL17-A levels, and carotid intima media thickness (CIMT), proteinuria, retinopathy, and the left ventricle mass index (LVMI).MethodsThe study included 159 patients diagnosed with and followed-up for primary hypertension … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
12
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 35 publications
(44 reference statements)
2
12
0
Order By: Relevance
“…It would appear that although controlled, hypertension can still be a trigger for immune stimulation, as was demonstrated by the close correlation between the duration of controlled hypertension and higher TLR4 expression. On the other hand, the duration of non-controlled hypertension was closely linked to a higher level of IL-17A in serum which is in line with other studies [33, 34] that found association between IL-17A and blood pressure values. Indeed, higher levels of IL-17A might be related to activated innate immunity, could be influenced by the used class of antihypertensive drugs or, as suggested by some authors might have protective role.…”
Section: Discussionsupporting
confidence: 81%
See 3 more Smart Citations
“…It would appear that although controlled, hypertension can still be a trigger for immune stimulation, as was demonstrated by the close correlation between the duration of controlled hypertension and higher TLR4 expression. On the other hand, the duration of non-controlled hypertension was closely linked to a higher level of IL-17A in serum which is in line with other studies [33, 34] that found association between IL-17A and blood pressure values. Indeed, higher levels of IL-17A might be related to activated innate immunity, could be influenced by the used class of antihypertensive drugs or, as suggested by some authors might have protective role.…”
Section: Discussionsupporting
confidence: 81%
“…Serum concentrations of IL-17A in our study were low in all patients, which is similar to some other studies [33]. Besides that, it is known that cytokines have short serum half-life and very often undetectable baseline levels.…”
Section: Discussionsupporting
confidence: 76%
See 2 more Smart Citations
“…It induces many cellular response and regulates inflammatory pathways depending on the cell type and micro environment [8]. sTWEAK's biological activity may vary by onset period of inflammation.…”
Section: Discussionmentioning
confidence: 99%